Simultaneous Selective Chlorination and Carbothermic Reduction of High-Iron Manganese Ore for the Recovery of Manganese Chloride and Metallic Iron - Dawei Yu; Fuhui Cui; Yunxiang Cong; Chunxi Zhang; Qinghua Tian; Xueyi Guo (Metals, 2019)
Metallurgical processing of low-grade manganese ore with high iron content is gaining increasing attention due to the gradual depletion of high-grade Mn ores, amid the difficulties in its efficient extraction for both Mn and Fe values in an environmentally-friendly manner. Attempting to tackle the difficulties, this paper describes an innovative process for selectively chlorinating and reducing the high-Fe manganese ore in a simultaneous manner, aiming to produce water-soluble MnCl2 and metallic Fe. After pre-mixing with carbonaceous reductant, CaCl2 and MgCl2 as the chlorinating agent, the Mn ore was heated at 1000 °C. As much as 89.4% Mn can be chlorinated in its water-soluble form, with dissolution of only 3.0% Fe. The presence of CaCl2 during carbothermic reduction resulted in significant promotion in both the Fe reduction rate and formation of large metallic Fe particles due to the segregation effect, facilitating subsequent separation. Selective Mn chlorination by MgCl2 took place with or without the involvement of SiO2, forming MgSiO4 or MgO, respectively.